Exercise on national health authority regulation: health sectorial rectory core - Robles Guerrero, Luis Ricardo (2013)
Health Sector Stewardship is an eigenfunction of the state, and is exercised in Peru and in most Latin countries through a Ministry of Health, which embodies the National Health Authority (NHA). Stewardship has three functions that are unique to the NHA: (a) steering, (b) regulation and enforcement, and (c) measurement of Public Health essential functions; and three functions which are shared with the regional Health Authority: (d) harmonization of service provision, (e) financing modulation, and (f) Health insurance guarantee. Stewardship in Health is a state power for taking responsibility for both population health and defense of health public good. Regulation and Enforcement become particularly important for proper and efficient performance of the authority because it has the role of cementing public health policies and coordinating the other functions of Stewardship. In view of this, the Ministry of Health, as the NHA, has the Regulation and Enforcement function as a valuable and important resource to meet its responsibility for population health safeguard and to improve sanitary conditions with equity.